The Palliative Care Outcome Scale: Turkish validity and Reliability Study - Vildan Kocatepe; Emel Emine Kayıkçı; Ülkü Saygılı; Dilek Yıldırım; Gülbeyaz Can; Güngör Örnek (Elsevier, 2020)
Objective: To examine the validity and reliability of the Turkish version of the Palliative Care Outcome Scale (POS). Methods: This methodological study consisted of 69 patients hospitalized in the palliative care (PC) service of three hospitals between June 2016 and August 2016, 69 carers who undertook continuously primary care of these patients, and 28 staff members working in the PC service and providing care to these patients. The data of the study were collected using the Personal Diagnosis Form, the POS. The scope, structure and criterion validity and internal consistency reliability of the scale were tested. Item analysis, Cronbach's alpha analysis, content validity ratio, confirmatory factor analysis for construct validity, criterion validity, patient validity, and intraclass correlation coefficient for the adaptation of outcomes of patient, carer, and staff groups were conducted. Results: The content validity ratio of the scale was found to be higher than 0.80 for patient, carer, and staff questionnaires. Item-total score correlation coefficients were determined between 0.27 and 0.72 for the items in the patient questionnaire, 0.33-0.67 for the carer questionnaire, and 0.34-0.72 for the staff questionnaire. The Cronbach's alpha reliability coefficients were determined as 0.64 for the patient questionnaire, 0.73 for the carer questionnaire, and 0.68 for the staff questionnaire. Conclusions: The Turkish version of the POS was determined to be a valid and reliable tool to be used for assessing the needs of PC patients in three dimensions in terms of the perspectives of patient, carer, and staff.